Money as a metaphor or the (non-) metaphor of money on two poems by Jorge de Sena - Maffei, Luis (2009)
Dealing with money in poetry is facing a radical problem: How should one treat such an extra-poetical issue? Jorge Sena deals with it, and such act represents a quite tense use of metaphor: Either literality or the senses are taken to high ambivalence levels. Two poems treat the theme “money” more directly: “Ode aos livros que não posso comprar” e “Tudo é tão caro!”. In the first, the presence of Marxist thought is clear and very influent on a beginner Jorge Sena. In the second, which was sophisticatedly built, some subtle intertexts with Camões are noticeable, a poet who is often present in the background of Sena’s lyric.